Optimal design of the neutron multiplicity counter based on metaheuristic algorithm - Lu, Yunfeng; Zhang, Quanhu; Yao, Qingxu; Wang, Yu (Frontiers in Physics, 2023)
The neutron multiplicity measurement and analysis method is a very important measurement and analysis method in the field of international arms control verification and nuclear safeguards, and its measurement accuracy depends to some extent on detector performance. In this paper, several newer current metaheuristic algorithms are introduced to achieve neutron multiplicity counter layout optimization by combining with MC (Monte Carlo) simulation software. The algorithm with the best finding ability is selected for the optimization of another detector layout. Based on the optimization results, k-means clustering analysis is introduced so that the optimized structure can be applied to neutron multiplicity measurements. The results show that the metaheuristic algorithm has good application capability for neutron detector layout optimization and can be further investigated.